KORELASI KECANDUAN MOBILE LEGENDS TERHADAP PRESTASI BELAJAR MAHASISWA - Diki Irwandi; Ruhban Masykur; Suherman Suherman (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2021)
The purpose of the study was to determine the correlation between the level of online game addiction and student achievement in the Mathematics Education Study Program, UIN Raden Intan Lampung. The method in this research was quantitative with the type of correlation research. The data collection technique used a questionnaire and tested it to see the validity and reliability. The data analysis technique in this study used the normality test using the Kolmogorov Smirnov method and the linearity test using SPSS software version 24.0, and hypothesis testing using a correlation test with a significant level of 0.05 or 5%. The study results were that of the 30 questionnaires tested, 25 questions were feasible to use. The reliability test has a value of rcount > rtable. The normality test got a significant value of 0.065 and 0.066 on online game addiction and learning achievement. So it can be said that there is a significant correlation between student achievement and online game addiction, and the value is 0.307, which means correlation